(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aims to examine the impact of nation branding dimensions, based on Anholt’s Nation Brand Hexagon model, on the international reputation of Qatar. It analyzes six core dimensions: governance, exports, tourism, investment and immigration, culture and heritage, and people. The study is grounded in the observation that Arabic literature addressing this relationship remains limited, despite Qatar’s continuous efforts to strengthen its global presence through investment, sports, diplomacy, energy, and media. The study adopts a descriptive-analytical approach combined with a case-study method, using a questionnaire distributed to academics, economic experts, international relations specialists, media professionals, and practitioners in the investment and tourism sectors, covering the period 2019–2025. Findings reveal a statistically significant positive effect of all six hexagon dimensions on Qatar’s international reputation, with sample respondents rating these dimensions highly. Governance was found to enhance reputation through efficient and credible public policy; investment and immigration attract talent and capital; while culture, heritage, tourism, and the image of the Qatari people all serve as key contributors to a positive international perception. Hosting major international events was also shown to significantly boost Qatar’s global visibility. The study recommends sustaining an integrated national strategy for nation-brand management, strengthening coordination among government entities, further developing the investment climate, supporting cultural initiatives, expanding public diplomacy programs, and conducting periodic studies to monitor the evolution of Qatar’s international reputation using recognized international indices.